Recent developments in the nomenclature, presence, isolation, detection and clinical impact of extracellular vesicles - Pol, E.; Böing, A. N.; Gool, E. L.; Nieuwland, R. (Journal of thrombosis and haemostasis, 2016)
Summary The research field of extracellular vesicles (EVs), such as microparticles and exosomes, is growing exponentially. The goal of this review is to provide an overview of recent developments relevant to the readers of the Journal of Thrombosis and Haemostasis. We will discuss nomenclature, the presence of EVs in fluids, methods of isolation and detection, and emerging clinical implications. Although research on EVs has been performed within the ISTH for over a decade, most of the recent research on EVs has been brought together by the International Society on Extracellular Vesicles (ISEV). To achieve an overview of recent developments, the information provided in this review comes not only from publications, but also from latest meetings of the ISEV (April 2015, Washington, DC, USA), the International Society on Advancement of Cytometry (June 2015, Glasgow, UK), and the ISTH (June 2015, Toronto, Canada).